CCNA Cyber Ops SECOPS 210-255 : complete video course - Santos, Omar (LiveLessons (Indianapolis, Ind.), 2017)
CCNA Cyber Ops SECOPS 210-255LiveLessons is a unique video product that provides a solid understanding of the key areas of knowledge required to pass the 210-255 SECOPS exam. This product walks through each topic of the Implementing Cisco Cybersecurity Operations exam blueprint, so you can gain the knowledge you need to pass the exam and start your career as a Security Operations Center (SOC) Security Analyst.